Textronic UHF RFID Transponder - Jankowski-Mihułowicz, Piotr (Sensors (Basel), 2021)
In order to respond the growing interest towards radio frequency identification textile transponders, the authors propose a new approach to design radio frequency identification (RFID) devices by introducing the RFIDtex concept. The coupling system of inductive loops is implemented in the textronic structure with the RFID interface in order to split the transponder into two independently manufactured components. Then both modules can be easily integrated into the RFIDtex tag. The presented simulation and measurement results prove the concept of manufacturing a relatively small antenna in the form of a meandered dipole sewn in with a single thread, and further, that can be connected to the RFID chip through the coupling system without galvanic junctions. The achieved parameters clearly indicate that the tag can correctly communicate with the read/write device as well as the coupling between its both parts works properly, and the impedance matching is possible in this case. The possibility of confectioning products with electronic identification tags at the textile factory site and improved resistance to the impact of environmental conditions are the main advantage of the proposed approach to the RFID devices designing. The RFIDtex transponder idea proposed by the authors was restricted in the patent no PL 231291 B1.